Investigating the link between narcissism and problem behaviors in adolescence. Issue 2 (17th February 2021) - Wetzel, Eunike; Atherton, Olivia E.; Robins, Richard W.
ABSTRACT: Previous research has shown that narcissistic traits such as exploitativeness, exhibitionism, and entitlement are associated with delinquency and aggression in childhood and adolescence. However, there is a paucity of longitudinal research examining these associations, and virtually no research examining other problem behaviors such as drug use and early sexual behavior. In this study, we extended previous research by testing whether two facets of narcissism, exploitativeness and superiority, assessed at age 14, predicted problem behaviors at age 16, while controlling for problem behaviors at age 14. We applied two-part count models to data from a longitudinal study of 674 Mexican-origin adolescents living in the United States followed over a two-year period from age 14 to 16. Adolescents with higher exploitativeness levels at age 14 were more likely to engage in drug use, commit delinquent acts, have sexual intercourse, and exhibit symptoms of conduct disorder at age 16, compared to adolescents with lower exploitativeness levels. Superiority had almost no associations with problem behaviors. Thus, exploitativeness may be one personality risk factor that underlies the development of multiple forms of problem behaviors in adolescence.